Authority, Autonomy, and Representation in American Literature, 1776-1865. - Patterson, Mark R. (Princeton legacy library., 2014)
From the Revolutionary War to the Civil War, a familiar scene appears and reappears in American literature: a speaker stands before a crowd of men and women, attempting to mitigate their natural suspicions in order to form a body of federated wills. In this important study of the relationship of literature and politics, Mark Patterson argues that this scene restates political issues in literary terms and embodies the essential problems of American democracy facing both politicians and writers: What is autonomy? How does representation work? Where does true authority lie? Beginning with the.